Design of 3D equilibria and coils for steady-state operation of tokamaks - Yihui Liang; Yao Zhou; Fanghao Dong; Caoxiang Zhu; Guodong Yu; Yuansheng Zhao; Ge Dong (Nuclear Fusion)
Inspired by the respective advantages of tokamaks and stellarators, we propose a quasi-axisymmetric (QA) tokamak-stellarator hybrid concept as a steady-state operation mode of standard tokamaks. Using stellarator optimization tools, we obtain compact 3D equilibria with good QA and sufficient (∼20%) rotational transform generated by external coils to replace current drive, with the rest (∼80%) generated self-consistently by the bootstrap current. The equilibria can be supported by 3D saddle coils that are compatible with typical tokamak coils and reasonably feasible from engineering perspectives. We consider and compare designs with either high-field-side or low-field-side shaping, and find that the latter is favorable for coil optimization but unfavorable for generating rotational transform and achieving good QA. These results highlight a relatively unexplored region in the space of toroidal fusion configurations.